Legitimacy and the Discourse of Revolution - Bilyi, O. (Социология: теория, методы, маркетинг, 2016)
The paper analyses the phenomenon of legitimacy crisis as a key factor for the revolutionary change. The latter opens the way to a new rationalisation of history, generating new political narratives and giving birth to a new system of laws. This system encounters resistance because of the old regime’s legal heritage and it is established by counter-power and imaginary institutions. Hence, the radical metamorphosis of political imagination produces certain forms of revolutionary legitimacy. The author develops a theoretical conception of revolutionary legitimacy, taking into consideration the interpretations of revolutionary practices around the w orld along with the experience of the Ukrainian Revolution of Dignity.